Pengaruh Promosi dan Kemudahan Penggunaan Terhadap Repurchase Intention Pada Layanan Online Food Delivery Shopee Food Yang Dimediasi Kepuasan Konsumen - Tiwik Mifsta Elfira; Nurhidayati Nurhidayati (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of Promotion and Ease of Use on Repurchase intention in the Shopee Food online food delivery service, mediated by Customer Satisfaction. Digital transformation has caused a significant shift in consumer behavior, increasing the reliance on practical and fast online food delivery services. The research employed an explanatory quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected from 100 Shopee Food users in Semarang using a questionnaire based on a five-point Likert scale. The findings indicate that Ease of Use is the most dominant factor influencing Repurchase intention, both directly and indirectly through Customer Satisfaction. Promotion significantly affects Customer Satisfaction, but its direct influence on Repurchase intention is not significant. However, Customer Satisfaction acts as a crucial mediator, significantly reinforcing the influence of both Promotion and Ease of Use on Repurchase intention. This research provides theoretical contributions regarding the mediating role of customer satisfaction in digital services and offers practical strategies for optimizing user experience and promotional efforts to enhance customer retention for online food delivery platforms